(untitled) (Journal of the College of Basic Education, 2022)
An experiment was conducted to test the effect of three treatments (Beauveria bassiana, the Iraqi probiotic and Aktara) to reduce the infection intensity of the cotton leafworm Spodoptera littoralis on the eggplant crop for the spring season 2013 in the plastic house at the College of Agriculture / University of Baghdad.The results showed that the Iraqi probiotic treatment gave the highest percentages of infected leaves and number of holes, reaching 0.44% and 67.4 holes/plant, respectively. While the treatment of the biological preparation of the fungus Beauveria bassiana showed the highest percentage of consumed leaf area and infected fruits, which amounted to 1.9% and 0.31 fruit / plant, respectively. The Aktara pesticide treatment showed the lowest percentage of infected leaves, consumed leaf area and the number of holes amounted to 0.4, 1.0%. and 60.8 holes/plant, respectively. while she was being treated